Effects of Heat Shock Protein 90 Inhibition In the Lungs - Mohammad A. Uddin; Khadeja-Tul Kubra; Jafrin Jobayer Sonju; Mohammad S. Akhter; Jois Seetharama; Nektarios Barabutis (Elsevier, 2020)
Inhibition of Hsp90 is associated with anti-inflammatory effects. We employed human lung microvascular endothelial cells to investigate the effects of the Hsp90 inhibitors 17-AAG, AUY-922 and 17-DMAG in the unfolded protein response (UPR) and viability of lung cells. Our observations indicate that moderate doses of those compounds trigger the activation of the UPR without inducing lethal effects in vitro. Indeed, AUY-922 triggered UPR activation in the lungs of C57BL/6 mice. UPR has been previously involved in the enhancement of the lung endothelial barrier function. Thus, the present study suggests that the barrier protective effects of Hsp90 inhibition in the lung microvasculature are highly probable to be associated with the activation of the UPR. Hence, the development of novel compounds which stochastically capacitate the repairing elements of UPR, may deliver new therapeutic possibilities against the severities of the acute respiratory distress syndrome.